The control of metal-silicon carbide contacts using a silicon interlayer. - Wai Yee Lee (2004)
The effect of Si interlayers within Ni-SiC contacts was studied using X- ray photoelectron spectroscopy (XPS), low energy electron diffraction (LEED) and scanning tunnelling microscopy (STM). Firstly an atomically clean surface was successfully obtained by depositing a 40A layer of Si onto the SiC surface, followed by an immediate anneal at 1000°C to re-evaporate the Si and remove surface contaminants. The interlayer was formed in ultra-high vacuum (UHV) conditions by depositing a known thickness of Si onto the clean SiC surface at room temperature. The metal contact was then produced by a sequential deposition of various Ni thicknesses onto the interlayer so that contact formation could be accurately monitored. These contacts were then annealed sequentially from 400°C to 1200°C. At each stage the process was characterised by XPS. Si interlayer thicknesses of 20A, 40A and 60A were tested. Results show that the consumption of Si atoms occurs, either from the Si interlayer or from the bulk SiC, with the evolution of Ni silicides and a Ni-Si-C ternary compound. In addition, chemical shifts associated with the formation of silicides and Fermi shifts (indicative of surface band bending) were also observed. When annealed at temperatures up to 1000°C, rapid formation of silicides is observed in the Si spectra, whilst the C spectra consisted of only bulk C and a small amount of free C. Conversely, for the Ni-SiC interface without a Si interlayer, the C spectra consisted of large amount of free C and hydrocarbon. As a result of annealing the interlayer samples, chemical shifts were observed as well as downward band bending, indicative of barrier lowering and complimentary to the generation of an Ohmic contact at these elevated temperatures. At 1200°C, all silicides had been re-evaporated leaving a carbon-rich surface, plus the formation of graphite on the surface. The electrical properties of the Ni-SiC contacts with and without Si interlayer were assessed using current-voltage (I/V) measurements. The contacts with a Si interlayer exhibit various behaviour from Schottky to Ohmic depending on the thickness of the Si interlayer. An Ohmic contact, which required no annealing was obtained when using a thick Si interlayer of 60A. However, Ni-Si-SiC Schottky contacts formed with 20A and 40A thick Si interlayers were shown to be able to operate, with Schottky barriers of ~1.7eV, up to 400°C higher than the normal Ni-SiC contact, indicating the superior control of these interfaces when Si is used as an interlayer.